PENGARUH MOTIVASI ORANG TUA TERHADAP HASIL BELAJAR SISWA KELAS X-5 DI SMA NEGERI 5 PEMATANGSIANTAR - Sahat Maruli Lumbantobing; Sotarduga Sihombing; Binsar Tison Gultom (JURNAL ILMIAH NUSANTARA, 2024)
This research focuses on parental motivation and student learning outcomes. This research aims to determine the presence or absence of parental motivation with student learning outcomes at SMA Negeri 5 Pematangsiantar and how big the relationship is. This type of research is correlational using a quantitative approach is 111 people, all clas X students at SMA Negeri 5 Pematangsiantar. The instrument used was a validity and reliability test. The data collection techniques used are ducomentation and questionnaires. The data was processed using the Normality test, so it can be concluded that the Normality test with the result obtained was 20,513 in the normal category. The result of the hypothesis test (t test) show that the thitung value is ttabel (6,282>1,659). So ho is rejected and Ha is accepted, which indicates that there is an influence of parental motivation on student learning outcomes at SMA Negeri 5 Pematangsiantar.